Tinjauan Kelengkapan Pengisian Sertifikat Medis Penyebab Kematian di Rumah Sakit Umum Pusat Persahabatan Januari 2014 - Enung Suhartini; Siswati Siswati (Indonesian of Health Information Management Journal (INOHIM), 2014)
Abstract Medical records is a file contain of documents about patients, identity examination, treatment, action and other services given to the patient.Registration death is recording of events experienced by people in a register in agencies to data processing population.Medical certificate cause of death is medical certificate that contains about the identity of someone and causes that leads people had death. The result of observation in RSUP Persahabatan, there are still lack in filling medical certificate cause death there is a factor causing incompleteness in filling medical certificate cause of death in RSUP Persahabatan like often switching doctor, and the absence of guidelines in filling in the doctor. The aim of this research is to find out incompleteness in filling medical certificate cause of death in RSUP Persahabatan. Of the results obtained completeness equal to 78 % and incomplete as much as 21, 5 % .While for babies obtained completeness 2.4 % and incomplete as much as 97, 6 %. ICD-10 Code in infants obtained the result of 0 %. Based on the observation that carried on the Health Information Management Department at RSUP Persahabatan on January 2014, quantitative analysis has not performed entirely on medical certificate cause of death by lack of human resource. Based on the observation that writers do, hence writers give advice of matter which is, should made guidelines charging medical certificate cause of death and dispensed to all nursery room inpatient. In addition socialized of the medical record to space inpatient procedures charging medical certificate cause of death with right also with legal aspect.Keywords: certificate, death, medicalAbstrakRekam  medis  adalah berkas yang berisikan  catatan dan dokumen tentang  identitas pasien , pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien. Pencatatan kematian adalah pencatatan kejadian yang dialami oleh seseorang dalam register dalam instansi pelaksana untuk pengolahan data kependudukan. Sertifikat medis penyebab kematian adalah sertifikat medis yang berisi identitas seseorang dan penyebab orang tersebut mengalami kematian. Dari hasil pengamatan di RSUP Persahabatan, masih terdapat kekurangan  pengisian sertifikat medis penyebab kematian. Beberapa faktor yang menyebabkan ketidaklengkapan pengisian sertifikat medis penyebab kematian adalah seringnya berganti dokter, dan tidak adanya pedoman pengisian di ruangan dokter. Tujuan penelitian ini untuk mengetahui ketidaklengkapan pengisian sertifikat medis penyebab kematian di RSUP Persahabatan. Dari hasil penelitian didapat kelengkapan sebesar 78% dan tidak lengkap sebesar 21,5%. Sedangkan untuk bayi didapat kelengkapan sebesar 2,4% dan tidak lengkap sebesar 97,6%. Kode ICD-10 pada bayi didapat hasil  0%. Berdasarkan hasil observasi yang dilakukan di Instalasi Manajemen Informasi Kesehatan RSUP Persahabatan pada Januari 2014, analisis kuantitatif belum dilakukan sepenuhnya pada sertifikat medis penyebab kematian disebabkan kurangnya tenaga pelaksana. Berdasarkan hasil observasi penulis, sebaiknya dibuat pedoman pengisian sertifikat medis penyebab kematian dan dibagikan ke setiap ruangan rawat inap. Selain itu Instalasi Manajemen Informasi Kesehatan perlu melakukan sosialisasi tentang tata cara pengisian sertifikat medis penyebab kematian dengan benar ke setiap ruang rawat inap.Kata kunci: sertifikat, kematian, medis